Prevention of swelling of liver tumor in Sprague-Dawley rat fed with the Kinu-Mozuku, an edible Japanese brown alga grown at seashores in Noto-peninsula. - Hayakawa, Kou; Nagamine, Takeaki (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Aim: Swelling of the tumor in the liver is difficult to stop by ordinary medicine. Then, new and safe drug preventing tumor-growth is required. Method: Three Sprague-Dawley rats, injected chemical carcinogen of diethyl- nitrosamine for 12 weeks, are then fed the edible brown-alga Kinu-Mozuku, grown at seashores around Noto peninsula, Japan, for 3 weeks. Results: No liver tumor is found in three Kinu-Mozuku-fed sample rat. On the contrary, all the three control-rats, fed without Mozuku, show very large tumor in their livers. This observation is statistically significant (P = 0.05 by Mann-Whitney’s U test). Conclusion: Japanese edible Kinu-Mozuku (Nemacystis decipiens) is proven to be the strong foodstuff/drug preventing enlargement of liver-tumor in the outbred rat. Thus, the edible fucoidan is expected to be the powerful and safe drug/medicine preventing and healing the human HCC and also the other intractable human cancers.